Adapting Civil Servants to the Digital Intelligence Era - Aldri Frinaldi; Syamsir Syamsir; Angga Putra Tri Rezeki; Wike Putri Melia (Journal of Education on Social Science (JESS), 2026)
The digital transformation of government in the era of digital intelligence is not simply a process of administrative digitization, but rather a shift in governance paradigm that demands the repositioning of civil servants as strategic actors in an ecosystem based on artificial intelligence (AI), big data, and algorithmic systems. This change requires civil servants to adapt multidimensionally not only mastering technology, but also possessing cognitive capacity, ethical sensitivity, and adaptive organizational capabilities. Ironically, amidst the flood of publications on digital transformation and Electronic-Based Government Systems (SPBE), studies that systematically place civil servant adaptation as the primary focus are still relatively limited and less dominant than those oriented towards technological and infrastructure aspects. Through a bibliometric analysis of 445 Google Scholar articles from 2021–2026 using VOSviewer and co-occurrence techniques, this study found that the themes of artificial intelligence, the digital era, and data dominate the knowledge structure, while the clusters of digital literacy, transformative leadership, organizational culture, and AI ethics emerge with much lower intensity. These findings confirm the technological bias in the discourse on bureaucratic digital transformation and the gap between system innovation and civil servant human resource readiness. If not balanced with strengthening adaptive capacity, integrating ethical values, and reforming organizational culture, digital transformation risks becoming trapped in procedural formalities and policy symbolism, instead of producing a responsive, accountable, and sustainable bureaucracy.